2013
DOI: 10.1002/bdm.1792
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Outcomes Sway Risky Decisions from Experience

Abstract: Whether buying stocks or playing the slots, people making real-world risky decisions often rely on their experiences with the risks and rewards. These decisions, however, do not occur in isolation but are embedded in a rich context of other decisions, outcomes, and experiences. In this paper, we systematically evaluate how the local context of other rewarding outcomes alters risk preferences. Through a series of four experiments on decisions from experience, we provide evidence for an extreme-outcome rule, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
175
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(200 citation statements)
references
References 53 publications
20
175
0
Order By: Relevance
“…The extra block of decisions from experience was included because past research indicated that decisions from description remain relatively stable across blocks, whereas preferences develop over training for decisions from experience as the outcomes associated with each option are learned (Ludvig & Spetch, 2011;Ludvig et al, 2014a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The extra block of decisions from experience was included because past research indicated that decisions from description remain relatively stable across blocks, whereas preferences develop over training for decisions from experience as the outcomes associated with each option are learned (Ludvig & Spetch, 2011;Ludvig et al, 2014a).…”
Section: Methodsmentioning
confidence: 99%
“…Each door/option appeared equally often on either side of the screen. Performance of lower than 60% on catch trials in either decisions from description or experience across the whole experiment was used as an exclusion criterion, following established protocol from previous experiments (Ludvig et al, 2014a(Ludvig et al, , 2014bLudvig & Spetch, 2011;Madan et al, 2014Madan et al, , 2015. Data from 18 of the 256 participants were thus excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One key characteristic of demonstrating the reversedreflection effect in experience-based choice is the intermixing of gain and loss decision trials within the same experimental task: participants on each trial are presented with a choice pair (certain and risky options) framed as either gains or losses (the Method section and for more details see, Ludvig et al, 2014). This intermixing of gain and loss trials appears to be crucial because when participants are presented with decision trials in a block-wise manner (repeated play from the gain trials followed by the loss trials or vice-versa), then the standard reflection effect is observed (see Erev, Ert, & Yechiam, 2008;Ert & Yechiam, 2010;Ludvig et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This intermixing of gain and loss trials appears to be crucial because when participants are presented with decision trials in a block-wise manner (repeated play from the gain trials followed by the loss trials or vice-versa), then the standard reflection effect is observed (see Erev, Ert, & Yechiam, 2008;Ert & Yechiam, 2010;Ludvig et al, 2014).…”
Section: Introductionmentioning
confidence: 99%